Service component in the mobile emergency and urgent care network - Santos, Givani Moraes; Nery, Adriana Alves; Constâncio, Tatiane Oliveira de Souza; Oliveira, Juliana Silva; Carmo, Érica Assunção; Silva, Vanessa Almeida Cardoso; Silva, Rafaela Almeida (Revista Cuidarte, 2019)
Introduction: External causes are a serious public health problem. We can highlight motorcycle accidents among them as a factor that increases sequelae and deaths. In this line of thought, the Urgent and Emergency Care Network was created to reduce the morbimortality rates of this population and make early care visible. Materials and Methods: Quantitative, descriptive and cross-sectional study with 1,812 patient care reports of motorcycle accidents. Results: Most victims were 20 to 59-year-old (66%) men (60.7%), the evening shift showed the highest frequency (40.2%), most cases occurred on the public road (86.8%). The most common type of injuries are skin wounds (45.9%). The pre-hospital procedures most commonly performed were immobilizations (47.2%) and healing procedures 17.7%. Discussion: Traffic accidents primarily affect male individuals of economically active age and have become a factor that increases sequelae. The average Response Time was approximately 30 minutes. Conclusions: Results can contribute to the Mobile Emergency Care Service by pointing out the need to (re)organize the service and the need to develop cross-sector actions that may go beyond the components of the urgent and emergency care network.How to cite this article: Santos G, Nery A, Constâncio T, Oliveira J, Carmo É, Silva V, et al. Atendimentos do componente móvel da rede de atenção às urgências e emergências. Rev Cuid. 2019; 10(3): e779. http://dx.doi.org/10.15649/cuidarte.v10i3.779
Keywords: Accidents, Traffic; Emergency Medical Services; Ambulatory Care; Epidemiology; Motorcycles.